Verifikasi Metode Analisis Penetapan Kadar Kaptopril Sediaan Tablet Menggunakan KCKT–PDA dalam Mendukung Regionalisasi Laboratorium BPOM - Laily Fauziah; Tuti Amalia As (Jurnal Pharmacopoeia, 2026)
Captopril is a drug in the Angiotensin-Converting Enzyme Inhibitor (ACE Inhibitor) class that is widely used in the treatment of hypertension and heart failure. Given its widespread use, the availability of reliable and validated analytical methods is crucial to ensure the quality, safety, and efficacy of pharmaceutical preparations containing captopril. Captopril analytical methods have been reported using various techniques, such as high-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry. However, before these methods are routinely used in the BPOM laboratory in Bengkulu, a method verification process is required to ensure that the adopted method meets analytical performance requirements under the conditions and equipment used.. The aim of this study was to verify the analysis method of Captopril in tablet preparations using HPLC with a PDA detector at the BPOM Bengkulu Laboratory. Verification was carried out using HPLC with a PDA detector at a wavelength of 220 nm, a 25 cm x 4.6 mm L1 column with a particle size of 5 um, using a mobile phase mixture of methanol; water; phosphoric acid (550; 450; 0.4) and a flow rate of 1 ml / minute in accordance with the Indonesian Pharmacopoeia edition VI. Verification results showed that the standard solution was detected at a retention time of approximately 4 minutes. In the specificity test, the Captopril standard and the tested sample produced peaks at identical retention times and spectra. The precision test provided a relative standard deviation (RSD) of 1.10%, the linearity test provided a correlation coefficient value of r = 0.9991, the accuracy test (recovery) at levels of 80%, 100% and 120% produced an average recovery of 97.55% with an acceptance range of 95% - 105%. In general, it can be concluded that the results of the verification of the analytical method for determining the levels of Captopril in tablet preparations meet the requirements and can be used in routine sample testing in the Laboratory.